Cytokine balance is restored as patient‐reported outcomes improve in patients recovering from chronic hepatitis C. (3rd May 2019) - de Avila, Leyla; Weinstein, Ali A.; Estep, J. Michael; Curry, Michael P.; Golabi, Pegah; Escheik, Carey; Birerdinc, Aybike; Stepanova, Maria; Gerber, Lynn; Younossi, Zobair M.
Abstract: Background & Aims: Chronic hepatitis C (CHC) has a negative impact on patient‐reported outcomes (PROs). Although most CHC patients who achieve sustained virologic response (SVR) show an improvement in PRO scores, some continue to experience impairment in PROs. The aim was to investigate if serum biomarkers (selected neurotransmitters and cytokines) are associated with changes in PROs in CHC patients who achieve SVR. Methods: Data were utilized from a prospective clinical trial of ledipasvir/sofosbuvir fixed‐dose combination. Chronic genotype 1 HCV subjects without cirrhosis (N = 40, age: 45.3 ± 11.5, 48% male, 90% white) were treated for 12 weeks open label with 97% achieving SVR24. PRO questionnaires included Short Form‐36 (SF‐36), Fatigue Severity Scale (FSS), Beck Depression Inventory‐II (BDI‐II), Chronic Liver Disease Questionnaire‐HCV (CLDQ‐HCV) and Functional Assessment of Chronic Illness Therapy‐Fatigue (FACIT‐F). Sera were used for measurement of selected neurotransmitters and cytokines. Data were collected at baseline and follow‐up week 24. Results: Changes in physical health correlated with changes in several biomarkers. BDNF negatively correlated with SF‐36 physical health summary score (rho = −0.34, P  < 0.05), SF‐36 physical functioning (rho = −0.34, P  < 0.05), SF‐36 bodily pain (rho = −0.39, P  < 0.05) and FACIT‐F physical well‐being (rho = −0.54, P  < 0.001). Changes in emotional well‐being (FACIT‐F) were positively associated with changes in serotonin (rho = 0.34, P  < 0.05), but negatively associated with changes in GABA and BDNF (rho = −0.4, P  = 0.01, and rho = −0.35, P  < 0.05 respectively). Conclusions: These data indicate relationships between PROs and serum biomarkers pre‐ and post‐SVR in CHC. These concomitant changes may have important clinical relevance.